Apoprotein B, Small‐Dense LDL and Impaired HDL Remodeling Is Associated With Larger Plaque Burden and More Noncalcified Plaque as Assessed by Coronary CT Angiography and Intravascular Ultrasound With Radiofrequency Backscatter: Results From the ATLANTA I Study. Issue 6 (19th November 2013) - Voros, Szilard; Joshi, Parag; Qian, Zhen; Rinehart, Sarah; Vazquez‐Figueroa, Jesus G.; Anderson, Hunt; Elashoff, Michael; Murrieta, Laura; Karmpaliotis, Dimitri; Kalynych, Anna; Brown, Charles; Schaefer, Ernst; et al.
Abstract : Background: Apoprotein B–containing lipoproteins are atherogenic, but atheroprotective functions of apoprotein A–containing high‐density lipoprotein (HDL) particles are poorly understood. The association between lipoproteins and plaque components by coronary computed tomography angiography (CTA) and intravascular ultrasound with radiofrequency backscatter (IVUS/VH) has not been evaluated. Methods and Results: Quantitative, 3‐dimensional plaque measurements were performed in 60 patients with CTA and IVUS/VH. Apoproteins, lipids, and HDL subpopulations were measured with 2‐dimensional (2D) gel electrophoresis, and correlation was assessed with univariate and multivariable models. ApoB particles were associated with a higher proportion of noncalcified plaque (NCP) and a lower proportion of calcified plaque (small, dense low‐density lipoprotein cholesterol and high‐density NCP: r =0.3, P =0.03; triglycerides and low‐density NCP: r =0.34, P =0.01). Smaller, dense, lipid‐poor HDL particles were associated with a shift from calcified plaque to NCP on CTA (α3‐HDL% and low‐density NCP: r =0.32, P =0.02) and with larger plaque volume on IVUS/VH (α4‐HDL%: r =0.41, P =0.01; α3‐HDL%: r =0.37, P =0.03), because of larger dense calcium (α4‐HDL%: r =0.37, P =0.03), larger fibrous tissue (α4‐HDL%: r =0.34, P =0.04), and larger necrotic core (α4‐HDL%: r =0.46, P <0.01; α3‐HDL%: r =0.37, P =0.03). Larger lipid‐rich HDL particles were associated with less low‐density NCP on CTA (α2‐HDL%: r =−0.34, P =0.02; α1‐HDL%: r =−0.28, P =0.05), with smaller plaque volume on IVUS/VH (pre‐α2‐HDL: r =−0.33, P =0.05; α1‐HDL%: r =−0.41, P =0.01; pre‐α2‐HDL: r =−0.33, P =0.05) and with less necrotic core (α1‐HDL: r =−0.42, P <0.01; pre‐α2‐HDL: r =−0.38, P =0.02; α2‐HDL: r =−0.35, P =0.03; pre‐α1‐HDL: r =−0.34, P =0.04). Pre‐β2‐HDL was associated with less calcification and less stenosis by both modalities. Conclusions: ApoB and small HDL particles are associated with larger plaque burden and more noncalcified plaque, whereas larger HDL and pre‐β2‐HDL particles are associated with plaque burden and less noncalcified plaque by both CTA and IVUS/VH.